The MET Oncogene: An Update on Targeting Strategies - Simona Gallo; Consolata Beatrice Folco; Tiziana Crepaldi (MDPI AG, 2024)
The MET receptor, commonly known as HGF (hepatocyte growth factor) receptor, is a focus of extensive scientific research. MET has been linked to embryonic development, tissue regeneration following injury, tumorigenesis, and cancer metastasis. These functions underscore its involvement in numerous cellular processes, including stemness, proliferation, motility, cell dissociation, and survival. However, the enigmatic nature of MET becomes apparent in the context of cancer. When MET remains persistently activated, since its gene undergoes genetic alterations, it initiates a complex signaling cascade setting in motion an aggressive and metastatic program that is characteristic of malignant cells and is known as "invasive growth". The expanding knowledge of MET signaling has opened up numerous opportunities for therapeutic interventions, particularly in the realm of oncology. Targeting MET presents a promising strategy for developing novel anti-cancer treatments. In this review, we provide an updated overview of drugs designed to modulate MET signaling, highlighting MET kinase inhibitors, degraders, anti-MET/HGF monoclonal antibodies, and MET-targeted antibody-drug conjugates. Through this review, we aim to contribute to the ongoing advancement of therapeutic strategies targeting MET signaling.